Immediate effect of semioccluded vocal tract therapy on acoustic parameters in transsexuals between 13 and 24 years - Sandoval Zúñiga, María Soledad; Fuenzalida C., Rodrigo; Pérez Z., Tanya; Torres Ch., Francisco (Revista de Investigación en Logopedia, 2019)
The purpose of this study is to describe the immediate effects of semioccluded vocal tract therapy on the acoustic parameters of transsexuals between 13 and 24 years old. This is a quantitative study, with a preexperimental design with pre and post test, whose dimension of temporality is transverse and whose scope is descriptive. The sample is composed of 8 transsexuals from 13 to 24 years old from Chillán, who have not received any treatment that can modify their vocal characteristics. The instrument used to measure the acoustic parameters is the PRAAT program (Boersma y Weenink, 2018). The results indicate that although the values of the acoustic parameters decreased, there is only an immediate effect in the acoustic parameters Jitter Local and Jitter Rap, because they present statistically significant differences between the measurements made before and after the therapy. According to the perturbation of the fundamendal frequency, the transsexuals’ voices became more deep and the harmonics-to-noise ratio approached the normal value after the therapy. It is concluded that the semioccluided vocal tract therapy has immediate effect on the Jitter acoustic parameter in male-to-female transsexuals from 13 to 24 years old and this therapy can be considered a viable and complementary alternative in the process of masculinization of the voice.
Keywords: Acoustic parameters; PRAAT; Semioccluded vocal tract therapy; Transsexual.